Efektifitas Spiritual Emotional Freedom Techniques (SEFT) terhadap Penurunan Tekanan Darah Pasien Hipertensi - Supatmi; Dian Novita Kumalasari; Siti Hanifatun Fajria; Agustiningsih (Badan Perencanaan Pembangunan Daerah Kabupaten Bantul, 2025)
Hypertension is a major global health issue with a high prevalence and significant contribution to morbidity and mortality. Emotional stress, psychological tension, and autonomic nervous system imbalance are known to exacerbate hypertension. However, accessible non-pharmacological therapies that address psychological and spiritual aspects such as the Spiritual Emotional Freedom Technique (SEFT) are still underutilized. This study aimed to analyze the effectiveness of SEFT therapy in reducing blood pressure among adults with hypertension. A quasi-experimental design with a one group pre test and post-test approach was used. A total of 45 respondents participated in a 2 week SEFT intervention. Blood pressure measurements were taken before and after the therapy. Data were analyzed using a paired t test to determine significant differences between pre-test and post test values. Most respondents were aged 56–70 years (71%), female (76%), and had a family history of hypertension (80%). Prior to the intervention, the majority were classified as having severe hypertension (56%), decreasing to moderate hypertension (58%) after the therapy. A significant reduction in blood pressure was observed, with an average decrease of 23.47 mmHg and a p value of 0.000. These findings indicate that SEFT effectively reduces both systolic and diastolic blood pressure through mechanisms of deep relaxation, stress reduction, and stabilization of the autonomic nervous system. SEFT is an effective complementary therapy for lowering blood pressure in hypertensive patients. This intervention is simple, safe, and easy to practice, making it a valuable adjunctive therapy to help control blood pressure and improve patients’ quality of life.